Code cody: A game-based learning platform for programming education - Mohd Suffian Sulaiman; Muhammad Haziq Ikhwan Jamaludin; Zuraidah Derasit (Journal of ICT in Education, 2023)
Programming courses are an essential and challenging component of the education of future computer specialists. Many beginners struggle with the abstract nature of these courses, resulting in high failure rates. Mastering programming languages is incredibly challenging for non-computer science students, as the subject can be unfamiliar and complex. The abstract concepts and problem-solving skills required in programming pose significant hurdles for newcomers. This article proposes a development project for game-based programming education at the primary school level. Features of the application that enable students to learn programming by solving problems while playing games. This project follows the game development life cycle (GDLC) methodology, which encompasses different stages. It begins with initiation, where the initial concept and vision for the game are defined. Next is the pre-production phase, where the concept is refined, and a detailed plan is created. The production phase involves implementing programming code. Then comes the testing phase. Finally, the game is released to the end user. The result shows that all the app functionality testing works well, and it can be concluded that this app can be used as an alternative to learn programming compared to the traditional approach.